Examining the relationship between audit committee share ownership and firm value: evidence from listed consumer goods firms in Nigeria - Suleiman Shatima; Kabiru Shuaibu (Indonesian Journal of Community Services, 2026)
This study examines the impact of audit committee share ownership on the firm value of listed consumer goods companies on the Nigerian Exchange Group (NGX). An explanatory research design was used, and the population of the study comprised all the consumer goods companies listed on the Nigerian Exchange Group for the years 2013-2022. Data for the study was obtained from the annual reports and accounts of all listed consumer goods companies for the period. The multiple regression analysis technique was used in analyzing the data. The findings reveal Audit committee share ownership has a significant positive impact on the firm value (TBQ). The study recommends that consumer goods companies should increase audit committee members' Share ownership to align their interests with the company's, promoting overall interest and enhancing firm value.